Length-Weight Relationship and Sex Ratio of Amblypharyngodon Mola in Dekar Haor of Sunamganj, Bangladesh - Das, PR; Uddin, MS; Islam, MS; Biswas, M; Mia, MR (Journal of the Asiatic Society of Bangladesh, Science, 2018)
The study was carried out to determine length-weight relationship and sex ratio of a freshwater fish Amblypharyngodon mola (Hamilton 1822) collected from Dekar haor of Sunamganj district during the period of January to August 2017. A total of 2000 fishes were collected for the study and categorized these fishes into three groups namely males, females and combined sexes. Among 2000 mola 777 were male and 1223 were female. Length-weight equations and the correlation coefficients obtained for males, females and combined ones were: males Y = –1.97 + 3.00X, r = 0.883; females Y = –2.30 + 3.41X, r = 0.914 and combined Y = –2.11 + 3.16X, r = 0.904. Female’s A. mola attained more weight with the increases in length. Value of correlation coefficient ‘r’ was 0.883 for male and exhibited highly positive correlation between length and weight. On the contrary, ‘r’ value for female was 0.914 and it had also strongly positive correlation between length and weight relationships. Length-weight relationship of A. mola for male, female and combined sexes showed allometric pattern of growth. Condition factor ‘K’ for male, female and combined sexes was 1.09, 1.05 and 1.06, respectively and indicated better condition of fishes. The highest sex ratio (1 : 2.05) was found in May and the lowest (1 : 1.33) was in February. Dominance of females over males throughout the year was observed with an average ratio of male and female 1 : 1.57. Therefore, results of the study indicate that the existing hydrobiological conditions of the haor are conducive for food availability, free movement, feeding and better growth of the fish. Asiat. Soc. Bangladesh, Sci. 44(2): 185-193, December 2018